2018
DOI: 10.1172/jci.insight.98420
|View full text |Cite
|
Sign up to set email alerts
|

Distinct biomarker signatures in HIV acute infection associate with viral dynamics and reservoir size

Abstract: Estimating the size of the viral reservoir is critical for HIV cure strategies. Biomarkers in peripheral circulation may give insights into the establishment of the viral reservoir in compartments not easily accessible. We therefore measured systemic levels of 84 soluble biomarkers belonging to a broad array of immune pathways in acute HIV infection in both antiretroviral therapy-naive (ART-naive) individuals as well as individuals who began ART upon early detection of HIV infection. These biomarkers were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 66 publications
4
29
0
Order By: Relevance
“…Similar observations of the cytokine storm have been reported in acute pathogenic SIV infections in rhesus macaques [8][9][10][11]. Even though the initiation of ART significantly reduces the plasma levels of inflammatory cytokines, some residual immune activation has been reported to persist even after the early initiation of ART [7,12,13].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar observations of the cytokine storm have been reported in acute pathogenic SIV infections in rhesus macaques [8][9][10][11]. Even though the initiation of ART significantly reduces the plasma levels of inflammatory cytokines, some residual immune activation has been reported to persist even after the early initiation of ART [7,12,13].…”
Section: Introductionsupporting
confidence: 73%
“…HIV infection is associated with immune activation which manifests in the elevation of numerous plasma cytokines and chemokines [1][2][3][4][5][6][7]. Notably, the elevation of some plasma cytokines occurs very early after infection, with acute HIV infection (AHI) being characterized by the onset of a cytokine storm in the period leading up to peak viremia [1,2,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the plasma cytokine profiles of HIV-infected individuals differ from the profiles of uninfected individuals. [64,65] Higher levels of IL-1, IL-6, IL-7, G-CSF and tumour necrosis factor α (TNFα) were detected in the plasma of HIV-infected patients. Pro-inflammatory cytokines TNFα, IL-1 and IL-6 and chemokines macrophage inflammatory protein (MIP)-1α, MIP-1β and RANTES were also found to be up-regulated in the bone marrow of HIV-infected individuals.…”
Section: Hiv-associated Auto-immune Reactionsmentioning
confidence: 99%
“…Immunological factors also play a role. The homeostatic proliferation (22) and clonal expansion (23)(24)(25)(26)(27)(28) of latently HIV-infected CD4 ϩ T cells directly influence the latent HIV reservoir size and dynamics, and evidence indicates that initial antiviral immune responses may also modulate reservoir establishment and persistence (29,30). A recent longitudinal study of an acute infection cohort reported that the pretherapy levels of key cytokines correlated with HIV DNA levels after 96 weeks of cART (29).…”
mentioning
confidence: 99%
“…The homeostatic proliferation (22) and clonal expansion (23)(24)(25)(26)(27)(28) of latently HIV-infected CD4 ϩ T cells directly influence the latent HIV reservoir size and dynamics, and evidence indicates that initial antiviral immune responses may also modulate reservoir establishment and persistence (29,30). A recent longitudinal study of an acute infection cohort reported that the pretherapy levels of key cytokines correlated with HIV DNA levels after 96 weeks of cART (29). Moreover, a previous analysis of the cohort evaluated in the present study identified baseline HIV-specific granzyme B responses, contributed mainly by human leukocyte antigen class I (HLA-I)-restricted CD8 ϩ T cells, to be significant negative correlates of the reservoir size at 48 weeks post-cART, as measured in terms of HIV proviral loads as well as the levels of replication-competent viral infectious units per million CD4 ϩ T cells (IUPM) (30).…”
mentioning
confidence: 99%